RANCANG BANGUN MESIN PRODUKSI ASAP CAIR DARI TEMPURUNG KELAPA BERBASIS TEKNOLOGI CYCLONE-REDISTILLATION - Muhammad Fathussalam; Angky Wahyu Putranto; Bambang Dwi Argo; Arta Harianti; Arsyika Oktaviani; Firda Pramesti Puspaningarum; Sellyan Lorenza Olanda Putri (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
The higher of coconut crop production in Indonesia has positively correlated with the amount of coconut shell waste produced which is difficult to decompose by microorganisms. Therefore, the utilization of coconut shell waste into charcoal and liquid smoke has been carried out in recent years. During this time, the conventional process of coconut shell-liquid smoke (CS-LS) takes 3-5 days and produces grade C liquid smoke in low volume. Hence, this study aims to design CS-LS production machine based on cyclone-redistillation technology which which can increase the volume of liquid smoke produced. In this study, the method used was engineering includes structural and functional design also testing performance both apparatus and product. The performance of CS-LS production machine was analyzed by volume for each grades (grade A, B and C). The result showed that CS-LS production machine based on cyclone-redistillation has been production according to specifications, with the total dimension of machine was 132 cm length, 100 cm width and 145 cm height. The volume of grade A CS-LS production was 65 L, whereas the grade B and C volumes was 10 L and 25 L, respectively, with a shorter total production time than conventional methods in SMEs. Therefore, design of CS-LS production machine based on cyclone-redistillation technology has great potentially applied in SMEs for producing liquid smoke in Indonesia to increase productivity and quality of CS-LS.